KUALITAS PELAYANAN PUBLIK BIDANG ADMINISTRASI KEPENDUDUKAN DI KECAMATAN WONOCOLO SURABAYA - Hidayattullah, Bagus Hanif (JPAP: Jurnal Penelitian Administrasi Publik, 2017)
Quality Public Service Administration Field of Population in Sub District Wonocolo Surabaya. This research is descriptive research using qualitative approach. Technique of data collection is done by observation, interview, and documentation. The research informants in this research are 1 person Head of Government Section as key informant, 1 person service officer in District Wonocolo and 3 people of service user society as supporting informant. From the result of the research, the quality of public service in population administration in Wonocolo district is seen from the aspects of tangible facilities, reliability, responsiveness, assurance, empathy (empathy), namely: (1) Wonocolo district in particular the public service part of the physical facilities and completeness of facilities and infrastructure is sufficient to support the productivity of population administration services in the District Wonocolo. (2) The community is satisfied with the services provided by Wonocolo Sub-district in the reliability aspect of the reliability in handling any community's complaints, reliable in terms of time and the accuracy of the service process. (3) Employees in terms of helping people who need services, especially people who are confused with the service has been seen between officers and visitors who communicate with each other. (4) Security in District Wonocolo has shown efforts to improve the quality of its services related to providing a sense of security for the community that is by placing a parking attendant who helped secure the situation in the parking. (5) Aspects of empathy (empathy), which is given the District Wonocolo is by giving a pleasant impression. It can be seen from the attitude of the officer who explained clearly about the service procedure and received criticism and suggestion wholeheartedly as an introspection for better service.Â Keywords : The Quality, Public Services, Sub-district Wonocolo